A new model for the bending of DNAs containing the oligo(dA) tracts based on NMR observations. - Katahira, M (1990)
The conformations of double-stranded d(GGAAATTTCC) x 2, d(GGTTTAAACC) x 2, d(CGCAAAAAAGCG)d(CGCTTTTTTGCG) and d(GCATTTTGAAACG)d(CGTTTCAAAATGC) have been studied by NMR spectroscopy. Analyses of cross peaks in NOESY spectra between the H2 of an adenine and the H1' of a deoxyribose in the 3'-neighbouring residue on the complementary strand revealed that the minor groove of the oligo(dA) tract is compressed gradually from 5' to 3' in each duplex. In view of this gradual compression of the minor groove along the oligo(dA) tract, it can be understood clearly why d(GGAAATTTCC)n x 2 and d(GAAAATTTTC)n x 2 are bent, and d(GGTTTAAACC)n x 2 and d(GTTTTAAAAC)n x 2 are not bent. The relative extents of bending of a series of d(AjN10-j)nd(N10-jTj)n sequences can also be understood systematically. Additionally, it was found that the TA step disturbed the compression of the minor groove of the oligo(dA) tract to some extent.